Environmental rights for future generations / Bridget Lewis. - Lewis, Bridget (Cambridge University Press, 2025)
This book presents readers with a new theory and practice of international human rights law that is designed to improve its protection of the environmental rights of future generations. Arguing that international law is currently unable to safeguard future generations from foreseeable environmental harm, Bridget Lewis proposes that the law needs to be reformed in the interests of achieving intergenerational justice. The book draws on different theories of intergenerational responsibility to articulate a fresh approach, revising both substantive principles of environmental rights and procedural rules of admissibility and standing. It looks at several case studies to explore how the proposed new approach would apply in relation to contemporary environmental challenges like fracking, deep seabed mining, nuclear energy, decarbonisation and geoengineering.